Financial Monitoring and Financial Intelligence: A Conceptual Approach to Distinguishing the Concepts - Egor K. Ovchinnikov (INTERNATIONAL CRIMINAL LAW AND INTERNATIONAL JUSTICE, 2026)
In this paper, the author carries out a research on a number of fundamental theoretical concepts used in the antimoney laundering, countering the financing of terrorism, extremist activity and countering the proliferation financing sphere. In particular, various approaches to understanding the term “financial monitoring” formed in the Russian doctrine are considered, and arguments are put forward justifying the necessity of their adjustment. The author suggests definition of the concept of “financial monitoring”, which makes it possible to unambiguously limit the range of its objects and subject composition. This paper also examines the concept of “financial intelligence” the definition of this term is formulated, examines its relationship with financial monitoring and other types of governmental activities.